R&D Activity and Financing Constraints: Evidence From Turkey - Gezici, Armağan; Orhangazi, Özgür; Yalçın, Cihan (Panoeconomicus, 2018)
We analyze the relationship between financing constraints and firms' R&D activity using a rich and comprehensive firm-level balance sheet and income statement data set of manufacturing firms in Turkey for the period 1996 to 2013. Using a firm-specific, time-varying financing constraints index, we find that financing constraints have a negative relationship with firms' R&D activity, after controlling for other determinants of R&D such as firm size, capital intensity and export market participation. Key words: R&D investment, financing constraint, credit constraint, internal funds, cash flow, Turkey. JEL: G30, G32, L20, O31, C33, E22.